A synoptic review of the aloes (Asphodelaceae, Alooideae) of KwaZulu-Natal, an ecologically diverse province in eastern South Africa - Abraham E. van Wyk (PhytoKeys, 2020)
The eastern, largely subtropical KwaZulu-Natal province of South Africa has a varied geology, climate and topography that ranges from high mountain peaks to beaches lapped by the Indian Ocean, so presenting a vast diversity of habitats that support a rich and diverse flora. Aloes are well represented throughout KwaZulu-Natal, with four genera [Aloe L., Aloiampelos Klopper & Gideon F.Sm., Aloidendron (A.Berger) Klopper & Gideon F.Sm. and Aristaloe Boatwr. & J.C.Manning] and 49 infrageneric taxa occurring in the province. The species range from trees that can reach a height of 20 m, through large, iconic single-stemmed plants, to miniatures of only a few centimeters tall. Fourteen of the aloes of KwaZulu-Natal are endemic and eleven near-endemic to the province. This paper presents a complete floristic treatment of the aloes of KwaZulu-Natal in the form of a synoptic review. Included are an identification key to the aloes that occur naturally in the province, morphological descriptions, notes on habitat, conservation status and threats to the survival of each taxon, species-level distribution maps and images of all the taxa, so providing for the first time, an up-to-date, illustrated account of aloe occurrence in this part of the subcontinent.